2011
DOI: 10.4278/ajhp.100628-qual-219
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Exposure among Hispanics/Latinos Living in Multiunit Housing: Exploring Barriers to New Policies

Abstract: Purpose Despite a high prevalence of voluntary home smoking bans and laws protecting Californians from exposure to secondhand smoke (SHS) in the workplace, many Hispanic/Latino (H/L) residents of multiunit housing (MUH) are potentially exposed to SHS from neighboring apartments. An advocacy/policy intervention was implemented to reduce tobacco-related health disparities by encouraging H/L living in MUH to implement voluntary policies that reduce exposure to SHS. This article presents findings from qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 14 publications
2
31
0
Order By: Relevance
“…In our study, a clear majority of elders living in the low-income housing properties surveyed support no-smoking policies for individual apartments, common areas and outdoor areas. Overall, our findings are consistent with other studies exploring support for smoke-free MUH policies among residents which ranged from 42 to 79 % support (Ballor et al 2013; Hennrikus et al 2003; Baezconde-Garbanati et al 2011; Hewett et al 2012; Licht et al 2012; King 2010). After adjusting for population characteristics, there were no differences among support for prohibitive smoking policies by exposure to SHS, smoking-related comorbidity (is) or race.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, a clear majority of elders living in the low-income housing properties surveyed support no-smoking policies for individual apartments, common areas and outdoor areas. Overall, our findings are consistent with other studies exploring support for smoke-free MUH policies among residents which ranged from 42 to 79 % support (Ballor et al 2013; Hennrikus et al 2003; Baezconde-Garbanati et al 2011; Hewett et al 2012; Licht et al 2012; King 2010). After adjusting for population characteristics, there were no differences among support for prohibitive smoking policies by exposure to SHS, smoking-related comorbidity (is) or race.…”
Section: Discussionsupporting
confidence: 91%
“…Survey size ranged from 142 10 to 5936 20 residents, with response rates ranging from 16% 11 to 86%. 10 Prevalence of cigarette smoking varied across studies, from 8% 10 to 48%. 17 Half of the studies focused on lowincome residents and/or low-income housing.…”
Section: Muh Resident Studies Study Methodologymentioning
confidence: 99%
“…10 Among current smokers, smoke-free home rules ranged from 6% 17 to 53%. 11 Two national studies revealed similar results on the percentage of MUH residents with smoke-free homes.…”
Section: Smoke-free Building Policies and Home Rulesmentioning
confidence: 99%
See 1 more Smart Citation
“…The association may reflect the presence of multiple exposures to immigrants and minority families with limited English skills who are more likely to live in crowded housing (Burr et al 2010; Standish et al 2010), have exposure to secondhand smoke (Baezconde-Garbanati et al 2011), experience food insecurity (Cutts et al 2011; Standish et al 2010), and develop poor overall health (Helm et al 2010). Others have likewise found infrastructure and neighborhood-level problems to be associated with poor child development, educational and health outcomes (Evans 2006; Grady 2011; Helm et al 2010; Patacchini and Zenou 2010; Tarter et al 2009).…”
Section: Discussionmentioning
confidence: 99%